2018
DOI: 10.5774/48-0-284
|View full text |Cite
|
Sign up to set email alerts
|

Nominal marking in Northern Tshwa (Kalahari Khoe)

Abstract: Languages of the Khoe family have a complex pronominal system that distinguishes three categories each for person, gender, and number. However, while languages of the Khoekhoe branch and the western subgroup of Kalahari Khoe obligatorily or optionally mark nouns and nominal classifiers for gender and number, the nominal marking system in eastern Kalahari Khoe appears to be undergoing serious reduction. This article discusses data on personal pronouns and nominal gender-number marking in four little-known North… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…None of these studies included a variety that exhibited the kind of divergence found in Tchoe. Fehn & Phiri (2017) posit a Southern and Northern Tshwa dialect cluster and although Tchoe shares features with both, it diverges signifi cantly due both to contact and language internal develop-ments. It is perhaps no coincidence that, geographically, the Thabala community lies somewhat in the middle of the two micro-areas.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…None of these studies included a variety that exhibited the kind of divergence found in Tchoe. Fehn & Phiri (2017) posit a Southern and Northern Tshwa dialect cluster and although Tchoe shares features with both, it diverges signifi cantly due both to contact and language internal develop-ments. It is perhaps no coincidence that, geographically, the Thabala community lies somewhat in the middle of the two micro-areas.…”
Section: Resultsmentioning
confidence: 96%
“…Recent studies on the diversity of the Kalahari Khoe languages in eastern Botswana have used descriptions of the pronominal systems to formulate hypotheses about about Tshwa-internal clas sifi cation (e.g. Chebanne 2014;Chebanne & Collins 2017;Fehn & Phiri 2017). None of these studies included a variety that exhibited the kind of divergence found in Tchoe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A noticeable exception is a detailed analysis of the Tjwao nominal system developed by Fehn and Phiri (2017).…”
mentioning
confidence: 99%